Impact of exclusive enteral nutrition on the gut microbiome of children with medical complexity. Issue 1 (4th June 2022) - Beauchamp‐Walters, Julia; Aleti, Gajender; Herrera, Lourdes; Debelius, Justine; Lima, Natalie; Dalal, Pritha; Hong, Suzi; Knight, Rob; Rhee, Kyung E.
Abstract: Background: Children with medical complexity (CMC) often require enteral tube feedings to meet their nutrition needs. Many, however, experience symptoms of feeding intolerance, such as vomiting and pain. The goal of this analysis was to examine the relationship between diet and the gut microbiome, controlling for medications, among CMC receiving enteral tube feedings, CMC consuming oral nutrition, and healthy controls. Given the variety of available commercial formula preparations, we were also interested in examining the impact of different formula types on the CMC microbiome. Methods: Fecal samples from 91 children (57 CMC and 34 healthy controls) were collected and analyzed. Parents completed clinical and dietary questionnaires. 16S ribosomal RNA amplicon sequencing was completed using the QIIME2 pipeline. Results: A significant decrease in alpha diversity among CMC receiving exclusive enteral nutrition (CMC EEN) compared with healthy controls (Shannon P = 0.006 and Faith's phylogenetic distance P = 0.006) was found that was not observed between CMC receiving oral nutrition and healthy controls. Significant differences in beta diversity were also observed between CMC EEN and healthy controls, with CMC EEN having a greater relative abundance of Enterobacteriaceae and obligate anaerobes. Differences were also noted between CMC EEN and CMC receiving oral nutrition (Aitchison distance P = 0.001); however, no differences were observed between CMC receiving oral nutrition and healthy controls. Conclusion: Despite similarities in medication profiles, CMC EEN have decreased alpha diversity and differences in beta diversity compared with healthy controls not observed in CMC receiving oral nutrition, highlighting the impact of diet over medications.